Correction: New insights on Celtic migration in Hungary and Italy through the analysis of non-metric dental traits. - Erica Piccirilli; Rita Sorrentino; Federico Lugli; Eugenio Bortolini; Sara Silvestrini; Claudio Cavazzuti; Sara Conti; Szabolcs Czifra; Katalin Gyenesei; Kitti Köhler; Károly Tankó; Antonino Vazzana; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0293090.].